2015
DOI: 10.1007/s00280-015-2871-z
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of neuroblastoma to the novel kinase inhibitor cabozantinib is mediated by ERK inhibition

Abstract: Treatment of neuroblastoma tumor cells with cabozantinib inhibits RET and ERK phosphorylation and is effective against neuroblastoma tumor cell lines alone and in combination with 13-cis-retinoic acid, topotecan, and temozolomide. Cabozantinib treatment is also effective in reducing tumor growth in vivo. Cabozantinib therefore represents a novel therapeutic agent for neuroblastoma, and further preclinical and clinical studies are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 42 publications
(57 reference statements)
3
29
1
1
Order By: Relevance
“…both of our luciferase transfected cell lines are sensitive to proliferation and migration inhibiting effects of cabozantinib, an inhibitor of VEGFR2 and MET kinases, with IC 50 s in the low micromolar range. Our findings were consistent with the recent results described by Zhang et al (37) where IMR-32 was one of the most sensitive neuroblastoma cell lines tested. In addition, we demonstrated that wound repair capacity was significantly reduced in IGR-N91-Luc cells and more importantly in the IMR-32-Luc cell line.…”
Section: Discussionsupporting
confidence: 94%
“…both of our luciferase transfected cell lines are sensitive to proliferation and migration inhibiting effects of cabozantinib, an inhibitor of VEGFR2 and MET kinases, with IC 50 s in the low micromolar range. Our findings were consistent with the recent results described by Zhang et al (37) where IMR-32 was one of the most sensitive neuroblastoma cell lines tested. In addition, we demonstrated that wound repair capacity was significantly reduced in IGR-N91-Luc cells and more importantly in the IMR-32-Luc cell line.…”
Section: Discussionsupporting
confidence: 94%
“…The neuroblastoma cell lines used in this study have been previously described [ 30 – 38 ] and were generously provided by Shahab Asgharzadeh (Children’s Hospital Los Angeles, Los Angeles, CA), Susan Cohn (The University of Chicago Children’s Hospital, Chicago, IL), Jill Lahti (St. Jude Children’s Research Hospital, Memphis, TN), John Maris (Children’s Hospital of Philadelphia, Philadelphia, PA), William Weiss (The University of California, San Francisco, San Francisco, CA) or were purchased from the American Type Culture Collection (ATCC; Rockville, MD). Cell lines were grown at 37° in 5 % CO 2 in appropriate media (Invitrogen, Carlsbad, CA) supplemented with 10 % heat-inactivated fetal bovine serum (FBS) (Life Technologies, Grand Island, NY), L-glutamine, sodium pyruvate, and non-essential amino acids [ 39 ]. All cell lines were authenticated by deoxyribonucleic acid (DNA) profiling prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…Patient tumor samples were homogenized and incubated for 30 min in radioimmunoprecipitation assay (RIPA) protein lysis buffer containing protease inhibitors (Sigma) and phosphatase inhibitors (Roche, San Francisco, CA) with homogenization every 10 min as previously described [ 39 ]. Lysates were centrifuged and supernatants were collected.…”
Section: Methodsmentioning
confidence: 99%
“…The neuroblastoma cell lines used in this study have been previously utilized by our laboratory2223, and were either purchased from American Type Culture Collection (ATCC, www.atcc.org) or were generously provided by Susan Cohn (The University of Chicago Children’s Hospital, Chicago, IL, USA), John Maris (Children’s Hospital of Philadelphia, Philadelphia, PA, USA), or the Children’s Oncology Group (COG) Cell Culture and Xenograft Repository (www.cogcell.org). Neural tumor cell lines U-87, U373, CHLA-02-ATRT and PFSK-1 were purchased from ATCC.…”
Section: Methodsmentioning
confidence: 99%
“…The viability of cells exposed to nifurtimox and BSO was determined using a modified methyl tetrazolium (MTT; Sigma) assay as previously described2223. 0.5–1.0 × 10 4 cells/well of exponentially growing cells were plated in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%